Effect of cable surface geometry and ice accretion shapes on the aerodynamic behaviour of inclined stay cables. Issue 216 (September 2021) - McTavish, Sean; D'Auteuil, Annick; Raeesi, Arash; Szilder, Krzysztof
Abstract: A wind-tunnel study has been conducted to evaluate changes in the aerodynamic behaviour of stay cables of a bridge due to ice accretion from freezing rain and, due to different cable surface geometries. Numerical simulations were performed to predict the three-dimensional ice shapes resulting from freezing rain for a variation of environmental conditions: wind speed, wind direction, air temperature, velocity of precipitation and duration of precipitation. Stay-cable models were fabricated using laser selective sintering for three different surface geometries (double helical fillet, concentric rings, and double helical strakes) with ice formed under the same environmental conditions. Additional models with the helical fillet geometry were fabricated to evaluate the effect of the air temperature at which ice was formed, the effect of wind direction during the precipitation event and the effect of the duration of the precipitation. The aerodynamic drag and lift forces acting on the models were measured for different wind speeds and cable-wind angles. The overall study evaluated the mean aerodynamic force coefficients of ten models in smooth flow, and two of the models were also tested in turbulent flow. The critical Reynolds number regime for the models of stay cable with ice accretion shapes occurred at a lower Reynolds number (below 100, 000) than for the un-iced cables and the drag coefficient was less sensitive to increases in Reynolds numbers than the equivalent un-iced cables. These effects were attributed to the combined role of the ice-shape in determining the separation point combined with the higher surface roughness of the ice. An important observation was that for the three surface geometries and the range of test conditions that were considered, the maximum drag coefficients for ice-accreted models ranged from approximately 1.1 to 1.3, and were up to 50% greater than those observed without ice. The model with helical strakes and ice accretion exhibited the highest drag coefficient and exhibited more variation in lift coefficient with changes in Reynolds number than the other two cable surface geometries. The aerodynamic forces of an ice-accreted model followed similar trends in smooth and turbulent flow, but the drag coefficients were greater in turbulent flow. The presence and shape of the ice appeared to have a more dominant effect on the separation behaviour of the models than the presence of turbulence (for an ice-accreted model). The aerodynamic coefficients did not change greatly between the cases where ice was accreted at − 0 . 5 ° C and − 1 . 5 ° C due to the similar ice shape and thickness near the separation locations. The ice shape formed at − 5 ° C was thicker but more localized and resulted in drag and lift coefficients that had greater variation with changes in the cable-wind plane. The effect of ice duration from 10 h to 20 h resulted in a increased variation in mean lift coefficient behaviour due to the asymmetric shape that resulted from the ice accretion parameters. Highlights: Stay cable aerodynamics were evaluated with and without freezing rain precipitation Conditions included many geometries, temperatures, precipitation angles, and time The critical Reynolds number regime occurred below Re = 100, 000 Drag coefficients were greater in turbulent flow than in smooth flow Drag coefficients increased by up to 50% with ice accretion The impingement point varied based on the precipitation conditions Site-specic considerations on icing and aerodynamics should be considered